Assessment of the Phytochemicals and Antibacterial Potential of Azadirachta indica (Neem) Leaves Extract against Selected Clinical Isolates - Agbo Anthony Ogbonnia; Mbah-Omeje Kelechi Nkechinyere; Eze Vincent C. (Darul Yasin Al Sys, 2026)
The rapid emergence of antimicrobial resistance has intensified the search for alternative therapeutic agents from medicinal plants. Azadirachta indica (neem) is widely recognized for its broad-spectrum biological activities; however, comparative evidence on aqueous and ethanolic leaf extracts against clinical isolates, accompanied by phytochemical profiling, remains limited. This study aimed to evaluate the phytochemical constituents and antibacterial potential of aqueous and ethanolic leaf extracts of A. indica against selected clinical bacteria. Mature neem leaves were collected, authenticated, air-dried, pulverized, and extracted using distilled water and ethanol. The extracts were concentrated using a rotary evaporator. Qualitative and quantitative phytochemical analyses were conducted using standard procedures, while antibacterial activity was assessed through the agar well diffusion method against Escherichia coli, Shigella sp., Lactobacillus sp., and Staphylococcus aureus. Zones of inhibition were measured, and minimum inhibitory concentrations were determined. Phytochemical screening revealed the presence of alkaloids, saponins, flavonoids, tannins, and glycosides, with glycosides being the most abundant constituent (22.85 ± 0.084) and flavonoids the least abundant (6.55 ± 0.087). At 200 mg/mL, the aqueous extract demonstrated higher antibacterial activity than the ethanolic extract, with inhibition zones of 27 mm against E. coli, 26 mm against Shigella sp., 23 mm against Lactobacillus sp., and 20 mm against S. aureus. The minimum inhibitory concentration results indicated resistance of E. coli to both extracts and reduced sensitivity of Lactobacillus sp. to the ethanolic extract. These findings suggest that aqueous extraction may be more effective for harnessing the antibacterial properties of neem leaves. This study contributes to phytomedicine and antimicrobial research by highlighting the potential of A. indica leaf extract as a cost-effective plant-based antimicrobial agent for managing bacterial infections, particularly in resource-limited settings.